The macroeconomic effects of global supply chain disruptions - David Finck; Peter Tillmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2023)
Highly interconnected global supply chains make countries vulnerable to supply chain disruptions. This paper estimates the macroeconomic effects of global supply chain shocks for the euro area. Our empirical model combines business cycle variables with data from international container trade. Using a novel identification scheme, we augment conventional sign restrictions on the impulse responses by narrative information about three episodes: the Tohoku earthquake in 2011, the Suez Canal obstruction in 2021, and the Shanghai backlog in 2022. We show that a global supply chain shock causes a drop in euro area real economic activity and a strong increase in consumer prices. Over a horizon of one year, the global supply chain shock explains about 30% of inflation dynamics. We also use regional data on supply chain pressure to isolate shocks originating in China. Our results show that supply chain disruptions originating in China are an important driver for unexpected movements in industrial production, while disruptions originating outside China are an especially important driver for the dynamics of consumer prices.
Keywords: E32; F14; F62; 330; Container Trade; Supply Chain; Inflation; Narrative Identification; Sign Restrictions